Chlorhexidine gluconate enhances the remineralization effect of high viscosity glass ionomer cement on dentin carious lesions in vitro - Patcharanun Borompiyasawat; Boonsong Putraphan; Sureerat Luangworakhun; Waleerat Sukarawan; Oranuch Techatharatip (BMC, 2022)
Abstract Background To compare the mean mineral density (MMD) and examine the remineralization of carious dentin after cavity disinfection with chlorhexidine gluconate (CHX) and restoration with high viscosity glass ionomer cement (H-GIC) in vitro. Methods Selective caries removal to leathery dentin was performed in 40 extracted primary molars. The samples were scanned using micro-computed tomography (micro-CT) to determine the MMD baseline and randomly divided into 4 groups (n = 10): Equia™ group, applied dentin conditioner and restored with H-GIC (Equia Forte™), CHX-Equia™ group, disinfected the cavity with 2% CHX before applying dentin conditioner and restored with H-GIC (Equia Forte™), Ketac™ group, restored with H-GIC (Ketac Universal™) and CHX-Ketac™ group, disinfected the cavity with 2% CHX before restored with H-GIC (Ketac Universal™). The samples underwent micro-CT scanning post-restoration and post-pH-cycling to determine their respective MMDs. One sample from each group was randomly selected to analyze by scanning electron microscopy (SEM). Results The MMD gain in the 4 groups post-restoration was significantly different between the Equia™ and CHX-Ketac™ groups (oneway ANOVA with Post hoc (Tukey) test, P = 0.045). There was a significant difference in MMD gain post-restoration between the Equia™ and CHX-Equia™ groups (Independent t-test, P = 0.046). However, the Ketac™ and CHX-Ketac™ group's MMD were similar. The SEM images revealed that the CHX-Ketac™ group had the smallest dentinal tubule orifices and the thickest intertubular dentin among the groups. However, the CHX-Equia™ group had thicker intertubular dentin than the Equia™ group. Conclusion Applying 2% CHX on demineralized dentin enhances the remineralization of the dentin beneath the restoration.